(untitled) (Dissertare, 2021)
The editorial addresses the discussion raised about the role of the State in the orientation of economic activity, a dispute that adopts as a concrete expression the clash between the positions represented by Keynesian policies and monetarist ideas. In the context of this controversy, the work presents a series of arguments that emphasize the need to recover the role of the State as a guide for the economy, highlighting this role in the context of the crisis caused by the emergence of the Covid-19 pandemic, given the importance of guaranteeing that the general interest prevails in aspects such as the production and application of vaccines. The editorial concludes that it is necessary to value public policies and investments that may have a greater impact on increasing the social rate of return, in alignment with the private rate of return.